Safer opioid supply: qualitative program evaluation - Haines, Marlene; O’Byrne, Patrick (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background As the overdose crisis in Canada continues to escalate in severity, novel interventions and programs are required. Safer Supply programs offer pharmaceutical-grade medication to people who use drugs to replace and decrease harms related to the toxic illicit drug supply. Given the paucity of research surrounding these programs, we sought to better understand the experience of being part of a Safer Supply program from the perspective of current participants. Methods We completed semi-structured interviews and surveys with Safer Supply participants in Ottawa, Canada. Interviews were audio-recorded, transcribed, and analyzed thematically. Descriptive statistics were used to report survey data. Results Participants most commonly discussed Safer Supply benefits. This included programs offering a sense of community, connection, hope for the future, and increased autonomy. Participants also described program concerns, such as restrictive protocols, inadequate drugs, and diversion. Conclusions Our research demonstrated that participants found Safer Supply to be effective and impactful for their substance use goals. While participants did discuss concerns about the program, overall, we found that this is an important harm reduction-based program for people who use drugs in the midst of the overdose crisis.